INDEPENDANT POWER SUPPLY SOURCE FOR THE STATION OF CATHODIC PROTECTION OF PIPELINES AGAINST CORROSION - Ezhov, Vladimir Sergeevich; Semicheva, Natalia Evgenievna; Berezin, Sergey Vladimirivich; Makhova, Veronika Vitalievna; Burtsev, Alexey Petrovich; Brezhnev, Artem Viktorovich; Drozhzhin, Roman Sergeevich (Journal of Applied Engineering Science, 2017)
The paper deals with the issues of direct conversion of thermal energy to electric one due to the use of the thermoelectricity effect to provide independent operation of a cathodic protection station when heat transfer fluids flow through pipelines. The experimental setup description, applied techniques and procedure, and the experimental results are presented. A possibility of generating electricity using thermoelectricity effect for a cathodic protection station independent power supply source is demonstrated.